2016
DOI: 10.17265/1537-1514/2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Value of Health Service—The Conceptual Mode

Abstract: A knowledge in the field of a perceived value in a marketing literature is in a steep progress. The concept of the perceived value is rerely founded in a health marketing literature. In the medicine health literature, the concept of a patient satisfaction and research models with direct relationship between service quality and patient satisfaction are used. Our conceptual model transfers knowledge from the other marketing sciences to the health marketing. In the article all elements of the conceptual model are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Değer algısının, duygusal bileşenlerinin yanı sıra bilişsel bileşenleri de vardır. Ancak algılanan değer, fayda ve fedakârlıklar arasındaki dengeyi gerektirmektedir (Pevec & Pisnik, 2016).…”
Section: Değer Algısıunclassified
“…Değer algısının, duygusal bileşenlerinin yanı sıra bilişsel bileşenleri de vardır. Ancak algılanan değer, fayda ve fedakârlıklar arasındaki dengeyi gerektirmektedir (Pevec & Pisnik, 2016).…”
Section: Değer Algısıunclassified
“…Dodds et al (2014) found that care quality and treatment efficiency were two most important value dimensions sought by CHA consumers. Similarly, Pevec & Pisnik (2016) pointed out that both price and perceived quality were two important value dimensions of health service.…”
Section: Functional Valuementioning
confidence: 99%